The Impact of Marketing Mix Elements toward Brand Equity through Brand Awareness and Brand Image as Mediators in Bakery Industry in Indonesia - Ivena Renata Chandra (iBuss Management, 2015)
As the factor accompanying the rise of GDP of people in Indonesia, consumption habit in having meal is as well shifting from traditional staple to wheat based product such as bakery products. Knowing from this phenomenon, it is known that bakery industry in Indonesia is on the business’s concern recently.The effort in having good brand equity in the consumer’s eyes surely will bring long term profit for the companies that are playing in this industry. In order to have a good brand equity, marketing mix elements which are price, intensity of marketing activities, store image, and price deals are believed can be the effective strategy in the business competition. Moreover, the existence of brand awareness and brand image as mediators are also playing a big role in achieving good brand equity.This market research is conducted by spreading 158 questionnaires to bakery consumers in Surabaya. This data is analyzed using regression with mediating analysis. The result is showing that intensity of marketing activities is not significantly impacting brand equity through brand awareness. Additionally, only price and store image give significant affect toward brand equity through brand image whereas intensity of marketing activities and price deals are not.Keywords: Bakery Industry, Marketing Mix, Brand Awareness, Brand Image, Brand Equity